Analisis Manajemen Risiko pada Proyek Konstruksi Pelabuhan: Kajian Literatur Sistematik - Haidar Haidar; Monalisa; Ardhani Agnas Pratama; Fery Siswantoro; Humiras Hardi Purba (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2022)
The development of an infrastructure in the region can have the effect of increasing people's access to resources so that the increase in productivity can encourage economic growth. Ports as sea transportation infrastructure have a very important and strategic role for industrial and trade growth and are business segments that can contribute to the economy and national development because they are part of the chain of transportation and logistics systems. For this reason, a risk analysis is needed so that the implementation of port construction can be completed on time, in terms of cost, quality and time. This study aims to analyze the risk of port construction using a systematic literature review method. Based on research results, risk in port construction projects is influenced by external non technical (22.807%), technical project (21.053%), external technical (21.053%), internal technical (18.421%), internal non technical (8.772%) and non technical project (7.895%).